Nirsevimab for preventing respiratory syncytial virus lower respiratory tract infections in infants: a systematic review and meta-analysis - Soudani, Samira; Bertizzolo, Lorenzo; Ghemmouri, Mehdi; Chappell, Mary; McCool, Rachael; Reddish, Katie; Miller, Paul; Barker, Erin; Fewster, Harriet (Frontiers in Public Health, 2025)
BackgroundRespiratory syncytial virus (RSV) causes lower respiratory tract infections (LRTIs) in infants, leading to substantial morbidity and mortality. Nirsevimab, a long-lasting monoclonal antibody, has been demonstrated to reduce RSV-related outcomes in randomized controlled trials (RCTs) and real-world settings. The object was to review the existing real-world evidence (RWE) on the effectiveness of nirsevimab in preventing RSV-LRTIs.MethodsSearches of six databases in addition to trial registries, HTA/regulatory agency webpages and conference abstracts were conducted in November 2024. Observational studies evaluating nirsevimab prophylaxis in infants during their first RSV season or high-risk infants in their second season were included. For outcomes evaluated by more than one study, feasibility assessment was conducted and, where appropriate, studies were combined in meta-analyses.ResultsSixteen studies reporting effectiveness outcomes were included. The studies were conducted across four countries (Spain, Italy, US and France), and included 141,550 infants. Nirsevimab showed significant effectiveness for preventing RSV-LRTI hospitalization (reduction in risk from hazard ratios and odds ratios of 84.5%; 95% CI: 73.6%−90.9%; I2: 0 and 73.7%; 95% CI: 42.3%−88.0%; I2: 0%, respectively), intensive care unit (ICU) admission (85.9%; 95% CI: 13.2%−97.7%) and ventilatory support (87.1%; 95% CI: 70.2%−94.4%). Nirsevimab was also effective in preventing RSV-LRTI visits in primary care (75.8%; 95% CI: 40.4%−92.7%) and emergency departments (87.9%; 70.3%−95.1%).ConclusionsReal-world evidence confirms the effectiveness of nirsevimab against RSV-LRTIs and underlines the public health impact of the intervention in preventing RSV-related health outcomes. There is no clear evidence that effectiveness differs for infants born in season (at birth immunization) compared with out of season groups, or that effectiveness varies in preterm infants compared to healthy term infants.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024591323.